1994
DOI: 10.1136/jmg.31.9.712
|View full text |Cite
|
Sign up to set email alerts
|

Familial half cryptic translocation t(9;17).

Abstract: A half cryptic translocation t(9;17) (p24.2; p13.3) was detected in a large family by fluorescence in situ hybridisation. Unbalanced karyotypes resulted either in lissencephaly and early death or in mental retardation, microcephaly, high arched palate, and deformities of the vertebrae. Some of the features observed in affected persons are characteristic of known syndromes involving either 17p or 9p. (JMed Genet 1994;31:712-714) ditional chromosomal segments. Out of five cases reported by 1990, four had unba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Originally, Miller-Dieker syndrome was thought to be an autosomal recessive disorder (Miller, 1963;Dieker et al, 1969;Garcia et al, 1978). However, with the introduction of the investigation of Miller-Dieker syndrome by prometaphase chromosome analysis (Dobyns et al, 1983) and later by the FISH techniques (Kuwano et al, 1991;Alvarado et al, 1993;Köhler et al, 1994;Masuno et al, 1995), it became clear that this syndrome was associated with a microdeletion of chromosome 17p13.3. Dobyns et al (1984), using the three families described in the original publications of Miller (1963), Dieker et al (1969), and Garcia et al (1978), showed that the Miller-Dieker syndrome in these cases was due to an unbalanced chromosome pattern resulting from a parental balanced translocation involving chromosome 17p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, Miller-Dieker syndrome was thought to be an autosomal recessive disorder (Miller, 1963;Dieker et al, 1969;Garcia et al, 1978). However, with the introduction of the investigation of Miller-Dieker syndrome by prometaphase chromosome analysis (Dobyns et al, 1983) and later by the FISH techniques (Kuwano et al, 1991;Alvarado et al, 1993;Köhler et al, 1994;Masuno et al, 1995), it became clear that this syndrome was associated with a microdeletion of chromosome 17p13.3. Dobyns et al (1984), using the three families described in the original publications of Miller (1963), Dieker et al (1969), and Garcia et al (1978), showed that the Miller-Dieker syndrome in these cases was due to an unbalanced chromosome pattern resulting from a parental balanced translocation involving chromosome 17p.…”
Section: Discussionmentioning
confidence: 99%
“…The patients in these families had not only a partial deletion of 17p13.3, but also a partial trisomy of the other involved chromosome. We compared the clinical manifestation of published cases with Miller-Dieker syndrome due to a familial translocation Alvarado et al, 1993;Köhler et al, 1994;Masuno et al, 1995) with our index case. The clinical features do not differ significantly.…”
Section: Discussionmentioning
confidence: 99%
“…FISH analysis is a valuable tool in the clarification of subtle reciprocal rearrange-ments25 26 and has been used to identify cryptic and half cryptic translocations in several cases of Miller-Dieker syndrome.9 [27][28][29] The study of Kuwano et al9 included a half cryptic 3q;17p and a full cryptic 8q;17p translocation. The case ofAlvarado et a127 represented a full cryptic 17p;19q translocation, while those of Kohler et a12P and Brecevic et a129 both represented half cryptic 9p; 1'7p translocations.…”
Section: Discussionmentioning
confidence: 99%
“…The other was ascertained via an index case with dup(17p) and a less severe phenotype [Köhler et al, 1994]. The translocations were detected by direct observation of G-banded chromosomes or by fluorescence in situ hybridization (FISH) using probes specific for the MDS critical region in 17p13.3, especially D17S379.…”
Section: Patients and Methods Ascertainmentmentioning
confidence: 99%